(untitled) (Journal of Current and Advance Medical Research, 2015)
Van Wyk and Grumbach syndrome is a rare condition characterized by breast development, uterine bleeding and multicystic ovaries in the presence of long-standing primary hypothyroidism. The patient with this syndrome was admitted in Shaheed Suhrawardy Medical College Hospital in November 2013. Here this rare and interesting case was reported. Journal of Current and Advance Medical Research 2015;2(1):24-27 DOI: http://dx.doi.org/10.3329/jcamr.v2i1.22586